Neuromyelitis optica: a demyelinating disease - Imran, Ayesha; Yelikar, Nitin Avinash; Borse, Sneha; Shah, Shreyash (International Journal of Contemporary Pediatrics, 2017)
Neuromyelitis optica (NMO) also known as Devic’s disease is a demyelinating disease. It involves the central nervous system and predominantly affects the spinal cord and optic nerves. It is characterised by episodes of optic neuritis and/or transverse myelitis. It is often confused with multiple sclerosis. NMO can occur rarely in children but cases of pediatric NMO need specific consideration owing to possible poor visual and motor outcome. We report a case of nine year male child admitted with history of fever followed by sudden weakness of body, sudden decline in visual acuity and involuntary passage of urine. The symptoms were reverted after the use of methylprednisolone. Clinical outcome was favourable with disappearance of sphincter troubles, improvement of visual acuity and progressive disappearance of motor troubles.